THE FACTORS AFFECTING THE ADOPTION OF DIGITAL PAYMENT SERVICES USING TRUST AS MEDIATING VARIABLE - Kurniasari, Florentina (Emerging Markets : Business and Management Studies Journal, 2020)
The advance of technology development today brings an innovation in the financial industries, especially in the sector of payment. The purpose of this research is to analyze the effect of personal innovativeness, security concerns and perceived enjoyment into customer adoption of digital payment services using trust as mediating variable. As a quantitative research, the study distributed questionnaires to 186 respondents who are customers who used digital payment platform in settling their business transactions. The data collection was furthered processed statistically using Structural Equation Method (SEM). The study showed that the customer decision to using the digital payment services had significantly influenced by trust variable, in which security concerns had the highest influence in creating the borrower’s trust.